Bringing children with hearing problems into inclusive education in the context of an educational cluster - Nazarova Dildora Asatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
currently, there are a number of problems in the implementation of the inclusive education system in our republic. The article will cover the issues of bringing children with hearing problems to inclusive education under the education cluster.